The determinants of information seeking behaviour and paying attention to earthquake-related information. (October 2020) - Tekeli-Yesil, Sidika; Pfeiffer, Constanze; Tanner, Marcel
Abstract: This study explores the process and determinants of finding information about earthquake-preparedness andof paying attention to earthquake-related information. Data were collected in Istanbul-Turkey, where an earthquake with a magnitude greater than 7 on the Richter scale is expected in the near future, using qualitative methods. Participants were mainly exposed to earthquake-related information following an earthquake. They seldom sought information, although those with higher socioeconomic levels and those who lived in higher risk zones were more likely to do so. There were clear differences between younger people, who did not share the collective memory of the 1999 earthquakes, and the older generations. Television was the main source of information and the internet the main source of further information. Participants were attracted by information that was based on real stories, had high quality visuals, was easily accessible, understandable, practical and that influenced the emotions. Due to the competing risks and concerns of daily life, the participants needed regular reminders about earthquake preparedness. The findings of the study presented valuable insight and hints, which might enlighten further arrangement needs considering earthquake risk communication among populations. The finding regarding the influence of collective memory among younger generations is new and will open the ways for further investigations.